2015
DOI: 10.1371/journal.pone.0118531
|View full text |Cite
|
Sign up to set email alerts
|

Aging with HIV vs. HIV Seroconversion at Older Age: A Diverse Population with Distinct Comorbidity Profiles

Abstract: ObjectivePeople aging with HIV might have different health conditions compared with people who seroconverted at older ages. The study objective was to assess the prevalence of, and risk factors for, individual co-morbidities and multimorbidity (MM) between HIV-positive patients with a longer duration of HIV infection, and patients who seroconverted at an older age. We compared estimates across both groups to a matched community-based cohort sampled from the general population.MethodsWe performed a case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 24 publications
3
82
1
5
Order By: Relevance
“…3 The incidence of infectious and non-infectious comorbidities and overall mortality have been found to be higher in HIV infected patients compared with HIV-negative ones. 4 Moreover the duration of HIV infection seems to be a stronger predictor of morbidity and non-infectious comorbidities compared with age at the diagnosis. 4 The main problems with older people are the low perception of risk and the stigma of speaking about sex, even with people sexually active.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The incidence of infectious and non-infectious comorbidities and overall mortality have been found to be higher in HIV infected patients compared with HIV-negative ones. 4 Moreover the duration of HIV infection seems to be a stronger predictor of morbidity and non-infectious comorbidities compared with age at the diagnosis. 4 The main problems with older people are the low perception of risk and the stigma of speaking about sex, even with people sexually active.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover the duration of HIV infection seems to be a stronger predictor of morbidity and non-infectious comorbidities compared with age at the diagnosis. 4 The main problems with older people are the low perception of risk and the stigma of speaking about sex, even with people sexually active. These 2 factors make more difficult to achieve HIV diagnosis and consequently they cause a delay that can lead to a severe immune deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This has implications for their long-term health and well-being, particularly if they present when their HIVinfection is advanced 10 . In Europe and North America, increased mortality among older people living with HIV is often attributed to increased prevalence of illnesses such as cardiovascular disease, and kidney and liver failure, which may worsen HIV disease progression 11 . These older people are also at greater risk of infectious diseases, such as tuberculosis 12 Providing easy access to testing, is a first step in getting people living with HIV on to treatment.…”
Section: Growing Numbers Of Older Adults Diagnosed With Hiv In Europementioning
confidence: 99%
“…However, it has been shown that aging PLHIV are subject to an increased level of multimorbidity as compared to the general population, encompassing increased risk of various conditions such as cardiovascular diseases, osteoporosis, chronic obstructive pulmonary disease (COPD), hypertension, types 2 diabetes mellitus and non-AIDS defining cancers [5][6][7]. While people with longer duration of HIV infection show an increased risk for multimorbidity as compared to people that acquire the infection at older age [8], older adults infected with HIV are at increased risk of short-term mortality, particularly if diagnosed at an advanced stage of the disease [9,10].…”
Section: Introductionmentioning
confidence: 99%